The Future Prospect of Rattan as Food Resources in Central Kalimantan - Kalima, Titi; Susilo, Adi (Proceeding International Conference on Global Resource Conservation, 2015)
Rattan plays an important role as food resources in the culture of the Dayak communities living near forest areas. Shoot of rattan is cooked by the Dayaks to make a dish